The environmental impact of scallop dredging in Breiðafjörður, West Iceland : a call for fishing technique and management reform - Chen, Kimberly Megan, 1987- (2012)
Ritgerðin er unnin við Háskólasetur Vestfjarða The fishery for C. islandica in Breiðafjörður was closed in response to the stock collapse around 2003. High rates of natural mortality, an increase in sea surface temperature, and inability to endure fishing pressure have been mechanisms suggested for the collapse. Fishing using inefficient or non-selective gear not only incurs direct mortality, but can also reduce individual fitness by applying physical damage and physiological stress. Reductions in fitness may compromise yield per recruit or lead to indirect mortality. The environmental impact of roller dredging was examined in two ways: (1) a framework for assessing cumulative impact on vulnerable marine taxa, and (2) modeling the effects on yield per recruit with the inclusion of different levels of indirect mortality. Results showed that total historical cumulative impact was highest for maerl (35.25%), echinoidea (35.25%), bivalves (33.24%) and alcyonacea (30.85%). As well, peak yield per recruit with the addition of indirect fishing mortality of 0.155 dropped to 27% of peak yield per recruit with no indirect fishing mortality. The certainty and significance of these results are discussed, along with strengths and weaknesses of both methods used. Then, a list of criteria was developed for fishing technique transform, and management actions are suggested. Veiðar á hörpudiski (C. islandica) í Breiðafirði voru stöðvaðar árið 2003 í kjölfar hruns í stofninum. Hár náttúrulegur dauði, hækkun sjávarhita og afleiðingar of mikillar sóknar hafa verið nefndar ástæður fyrir hruninu. Í þessari ritgerð voru áhrif veiðarfærisins (plógs) metin. Umhverfisáhrif plógsins voru metin á tvo vegu: (1) rannsóknaraðferð er metur uppsöfnuð umhverfisáhrif á viðkvæma lífveruhópa og (2) líkan sem metur afrakstur á nýliða að teknu tilliti til óbeins fiskveiðidauða af völdum veiðarfæris. Niðurstöður leiddu í ljós að uppsöfnuð neikvæð áhrif voru hæst hjá kalkþörungum (35.25%), ígulkerjum (35.25%), samlokum (33.24%) og náhönd (30.85%). ...